Service Business Revenue Analysis: Empirical Study on SME Sini Sa Clean - Rahmat, Abdul; Yunus, Rita; Sading, Yunus; Yunus, Santi; Jaya, Andi Herman; Paskual, Meyti Ferdiana (Manunggal Halim Jaya, 2024)
Small and Medium Enterprises, abbreviated as SMEs, play an important role in enhancing the economic growth of a country. They function to increase local income by meeting the community's needs for products and providing job opportunities. Sini sa Clean is one of the SMEs operating in the cleaning services sector in the city of Palu. Sini sa Clean offers room cleaning services, mattress cleaning, and sofa cleaning. This research aims to analyze the income and business feasibility of Sini sa Clean. The data analysis method used is the income analysis formula consisting of Total Cost (TC), Total Revenue (TR), and Profit (π). Meanwhile, to calculate business feasibility, the Revenue Cost Ratio (R/C Ratio) formula is used. Based on the research results, the average revenue for Sini sa Clean's cleaning service business is Rp. 2,521,000 per month, with total production costs amounting to Rp. 1,548,000 per month. These production costs consist of fixed and variable costs. From the data analysis results, the income generated by Sini sa Clean's business is Rp. 973,000 per month. Based on the business feasibility calculation (R/C Ratio), a value of 1.62 is obtained, which means 1.62 > 1. This indicates that for every Rp. 1 spent, there is a return of Rp. 1.62, making the revenue greater than the capital invested. Therefore, the cleaning service business of Sini sa Clean can be considered profitable, feasible to continue, and worth expanding.